Overcoming Spectral Interferences in the Determination of Cadmium in Various Food Materials Using Isotope Dilution Inductively‐coupled Plasma Mass Spectrometry#. (20th February 2015) - Kim, Sook Heun; Lim, Youngran; Hwang, Euijin; Yim, Yong‐Hyeon
<x xml:space="preserve">Abstract</x> Double isotope dilution inductively‐coupled plasma mass spectrometry (ID ICP/MS) is widely used for the certification of trace elements in candidate reference materials by many national metrology institutes because it allows accurate and reliable determination of the elemental content in complex matrices of food samples. The presence of isobaric interferences, however, may cause nonnegligible biases in isotope ratio measurements, giving erroneous analytical results. In this study, a matrix separation was carried out using anion exchange chromatography to eliminate isobaric interferences so that an accurate determination of Cd in candidate reference materials could be obtained. Synthetic blends of Cd and interfering elements were used to optimize the matrix separation conditions. The isobaric interferences for cadmium isotopes in various food samples were investigated using the optimized method. Without matrix separation, a significant bias, up to 18%, was observed in a soybean sample. It was about 3% in an herb sample. With the proper selection of isotopes and elimination of isobaric interferences, Cd concentrations in food candidate reference materials were robustly certified.